Impact of Cyber security Measures on Risk Mitigation, with the Mediating Role of Data Protection - Akhtar Ali; Nayyab Zulfiqar; Muhammad Usama; Rana Muhammad Ikraam (Indus Journal of Social Sciences, 2025)
This research paper considers how cybersecurity and data protection method influence the reduction of risk to a company. It also considers how technologies like firewalls, encryption, and multi-factor authentication work to reduce the incidence of cyber-attacks and data leaks. Scientists have also stepped into thinking about the use of data protection to make the various cybersecurity procedures more effective. Stemming from a quantitative research paradigm, authors distributed questionnaires to IT managers together with cybersecurity specialists as well as data protection officers within various sectors. This paper examines the correlation between cybersecurity measures, data security and subsequent risk reduction by employing regression. In total, it is possible to conclude that comprehensible data protection policies, as well as cybersecurity measures, contribute to the reduced levels of risks for an organization. Also, it is supposed that data protection contributes to the success of cybersecurity actions, and thus it is proof of how these two disciplines are inseparable and should be used as two integrated components of the risk management system. The work done in this study reveals that corporations with proper data security measures have greater chances of handling cyber dangers and minimizing operational risks. That these results bear significant implications for policymakers and the business aiming at improving cybersecurity systems and data protection techniques.